2021
DOI: 10.1180/mgm.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

An in situ, micro-scale investigation of inorganically and organically driven rare-earth remobilisation during weathering

Abstract: At present, a significant portion of rare-earth elements (REEs) are sourced from weathering profiles. The mineralogy of the protolith plays an important role in controlling the fate of REEs during weathering, as accessory minerals contain the bulk the REE budget in most rocks, and different minerals vary in their susceptibilities to weathering processes. REE supergene deposits (‘adsorption clay deposits’) are associated with deep weathering in tropical environments, which often precludes characterisation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Scanning electron microscopy–energy-dispersive spectrometry (SEM-EDS) analysis of the tailing (Figure S3) also indicated the coexistence of Ce and Fe at various spots. Several studies have confirmed the high elemental affinity among Ce, Fe, and Mn in geochemical processes, such as the formation of regolith-hosted REE deposits, REE-rich deep-sea sediments, and hydrogenetic ferromanganese crusts . Considering the weight percentage and REE concentration of the fractions, the particles in the size range of +0.08–0.15 mm with the approximate concentration of 982.3 mg kg –1 were selected for further recovery experiments, and the details of individual REE concentrations and main chemical composition are listed in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Scanning electron microscopy–energy-dispersive spectrometry (SEM-EDS) analysis of the tailing (Figure S3) also indicated the coexistence of Ce and Fe at various spots. Several studies have confirmed the high elemental affinity among Ce, Fe, and Mn in geochemical processes, such as the formation of regolith-hosted REE deposits, REE-rich deep-sea sediments, and hydrogenetic ferromanganese crusts . Considering the weight percentage and REE concentration of the fractions, the particles in the size range of +0.08–0.15 mm with the approximate concentration of 982.3 mg kg –1 were selected for further recovery experiments, and the details of individual REE concentrations and main chemical composition are listed in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Factors that control how the REEs are mobilized, transported or deposited in geological fluids include pH, temperature, ligand activities (i.e., of chloride, sulfate, fluoride, carbonate, phosphate and organic species), the availability of oxidising or reducing agents, crystallographic controls and adsorption onto clays or suspended particulate matter (Aubert et al 2001;Borst et al 2020;Li et al 2022a, b;Liu et al 2018;Liu et al 2017;Louvel et al 2022;Migdisov et al 2016;Nelson et al 2003). Many of these factors are challenging to constrain in regolith due to the poor preservation of fluid inclusions, small mineral grain-sizes and dynamic (bio)geochemical processes (Kalintsev et al 2021). Nevertheless, certain minerals and textures can provide insight into the conditions of weathering.…”
Section: Nature Of the Weathering Fluidmentioning
confidence: 99%
“…Particularly, there is an increasing focus on the processes that govern REE behaviour in supergene systems (Andersen et al 2017;Borst et al 2020;Cook et al 2023;Hutchinson et al 2022;Li et al 2022a, b;Wu et al 2023). This is due to the complexities introduced by chemical weathering, overprinting, primary mineral destruction and multiple REE fractionation processes that result from combinations of aqueous complexation with organic and inorganic ligands, pH-Eh variation, biota, climate, authigenic mineral precipitation, clay mineral adsorption, and groundwater flow (Andersen et al 2017;Borst et al 2020;Chapela-Lara et al 2018;Cook et al 2023;Kalintsev et al 2021;Ondrejka et al 2018;Ram et al 2019;Wu et al 2023;Zhukova et al 2021). Supergene processes also enriched some of the world's most important REE deposits, such as Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, on Earth's surface, rare earth elements (REEs) are slightly enriched in mineral coatings compared with the underlying bedrock (Thiagarajan and Lee, 2004;Goldsmith et al, 2014;Xu et al, 2019). Particularly, the enrichment degree of cerium (Ce) in mineral coatings can reach 12 times, and Ce is concentrated in Mn-rich regions (Kalintsev et al, 2021). The occurrence of Ce is either in the form of interlayer cations in birnessite, or as Ce(OH) x nanoclusters adsorbed on corners of birnessite layers.…”
Section: Photocatalytic Oxidation Of Water By Mn Oxidesmentioning
confidence: 99%